CONSTRUCTION OF SELF DUAL CODE OVER FINITE ABELIAN GROUP - RHEZA SETIAWAN (NIM : 10110018), MICHAEL
For systematic group code over finite field the following result is well known: If [IjP] is the generator matrix then the generator matrix of its dual code is [􀀀PT jI]. A.A.Zain and B.Sundar Rajan (1997) have generalized that result for Finite Abelian Group. In their paper, it is shown that if endomorphism which characterized group code over Finite Abelian Group is given,then the endomorphism which characterized its dual code can be easily known. Furthermore, in that paper, there is a characterization about self dual code. On this research, the writer will give some explicit example about self dual code over Finite Abelian Group. Moreover, the writer will assess weight distribution from the self dual code over Finite Abelian Group produced.